Antioxidant and anti-inflammatory function of walnut green husk aqueous extract (WNGH-AE) on human hepatocellular carcinoma cells (HepG2) treated with t-BHP - Zheng-Qiang Li; Yu-Ting Gao; Chen-Fa Zhao; Rui An; Yan-Lv Wu; Zhi-Pang Huang; Ping Ma; Xu Yang; Rong She; Xiao-Yan Yang (PLoS ONE, 2025)
Oxidative damage, oxidative inflammation, and a range of downstream diseases represent significant threats to human health. The application of natural antioxidants and anti-inflammatory agents can help prevent and mitigate these associated diseases. In this study, we aimed to investigate the effectiveness of walnut green husk (WNGH) as an antioxidant and anti-inflammatory agent in an in vitro setting. HepG2 cells were treated with tert-butyl hydroperoxide (t-BHP) to establish a cellular model of oxidative damage and inflammation. We assessed the biocompatibility of walnut green husk aqueous extract (WNGH-AE) on HepG2 cells using MTT and LDH assays (WNGH-AE concentration: 0.05, 0.1, 0.2, 0.4, 0.8, 1.6, 3.2, 6.4, and 12.8 mg/mL). Additionally, we measured intracellular oxidative stress indicators, such as ROS and 8-OHdG, along with inflammatory factors TNF-α and IL-1β through ELISA to evaluate the antioxidant and anti-inflammatory capacity of WNGH-AE (concentration: 0.025, 0.05, 0.1 mg/mL) in HepG2 cells. We also determined the free radical scavenging capacity of various extracts of WNGH using DPPH and ·OH methods. The total phenols, total polysaccharides, and total flavonoids in WNGH-AE were analyzed using the Folin-Ciocalteu’s reagent, the phenol-sulfuric acid method, and the spectrophotometry, respectively. The bioactive components of WNGH-AE were analyzed using LC-MS/MS. Our results demonstrated that WNGH-AE was highly biocompatible with HepG2 cells. The antioxidant effect of WNGH-AE involved the scavenging of intracellular ROS, while its anti-inflammatory effect was linked to the down-regulation of the NF-κB pathway. Compared to other extractants (ethyl acetate, n-butanol, 75% ethanol, and petroleum ether), WNGH-AE exhibited the strongest free radical scavenging ability. Through LC-MS/MS analysis, we identified 403 compounds in WNGH-AE, with gentisic acid being the most abundant and possessing high antioxidant capacity, suggesting it may be a key active component contributing to the antioxidant activity of WNGH-AE. In conclusion, our findings indicate that WNGH-AE is a natural, high-quality antioxidant and anti-inflammatory biomaterial deserving further research and development, with significant potential applications in healthcare. (311 words)